2007
DOI: 10.1038/sj.ejcn.1602742
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sources of reporting error using measured food intake

Abstract: Objective: To investigate the magnitude and relative contribution of different sources of measurement errors present in the estimation of food intake via the 24-h recall technique. Design: We applied variance decomposition methods to the difference between data obtained from the USDA's Automated Multiple Pass Method (AMPM) 24-h recall technique and measured food intake (MFI) from a 16-week cafeteria-style feeding study. The average and the variance of biases, defined as the difference between AMPM and MFI, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 20 publications
(24 reference statements)
2
58
0
2
Order By: Relevance
“…In contrast, mean energy obtained from 2 different food-frequency questionnaires (FFQ) significantly underestimated TEE, by Ȃ27% on each FFQ. Similar results were reported by Rumpler et al (11) in a sample of 12 normal-weight men; mean EI collected by the AMPM did not differ significantly from measured food intake. However, energy was underreported by 22% on an FFQ in this same sample (27).…”
Section: Validity Of the Automated Multiple-pass Methods For Assessingsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, mean energy obtained from 2 different food-frequency questionnaires (FFQ) significantly underestimated TEE, by Ȃ27% on each FFQ. Similar results were reported by Rumpler et al (11) in a sample of 12 normal-weight men; mean EI collected by the AMPM did not differ significantly from measured food intake. However, energy was underreported by 22% on an FFQ in this same sample (27).…”
Section: Validity Of the Automated Multiple-pass Methods For Assessingsupporting
confidence: 79%
“…In recent studies using the AMPM, mean energy intake (EI) was accurately reported for small groups of normal-weight men (11) and women (12).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that our absolute estimates of total 24-h beverage energy consumed were lower than true intakes. Proportional intake may also have been underestimated, because sweetened beverages, in particular, may have been underreported because of the possible social undesirability of their consumption and poor recall of consumption frequency and volume (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies point athlete of different modalities [25][26][27][28], as well as the general population [29], use to misreport the energy intake in order to describe practices similar to their pairs. For instance, obese people tend to report energy intake similar to non-obese people [30], and athletes tend to report values similar to non-athletes [31].…”
Section: Discussionmentioning
confidence: 99%